2020
DOI: 10.1088/1674-1056/abad26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Re, Ta, andWin [110] (001) dislocation core of γ/γ′ interface to Ni-based superalloys: First-principles study*

Abstract: The strengthening effects of alloying elements Re, Ta, and W in the [110] (001) dislocation core of the γ / γ′ interface are studied by first-principles calculations. From the level of energy the substitution formation energies and the migration energies of alloying elements are computed and from the level of electron the differential charge density (DCD) and the partial density of states (PDOSs) are computed. Alloying elements above are found to tend to substitute for Al sites γ′ phase by analyzing the substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For instance, the density functional theory (DFT) can describe accurately the physical properties in multiple materials. [1][2][3][4][5] However, in this method, the calculation time efficiency in the processes is mainly determined by the diagonalization routines. [6] Besides, another approach, the Thomas-Fermi (TF) theory [7,8] allows the determination of the electronic structure with a very simple way in comparison to the DFT.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the density functional theory (DFT) can describe accurately the physical properties in multiple materials. [1][2][3][4][5] However, in this method, the calculation time efficiency in the processes is mainly determined by the diagonalization routines. [6] Besides, another approach, the Thomas-Fermi (TF) theory [7,8] allows the determination of the electronic structure with a very simple way in comparison to the DFT.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first principles method has been used to study the strengthening effect of alloying elements Re, Ta, and W in the γ/γ ′ interface [110] (001) dislocation core. [18] By analyzing the substitution formation energy and alloy-element migration energy, it was found that the stability of [110] (001) dislocation core is enhanced by adding Ta, W, and Re. Rapid solidification was widely used as an important material preparation method to enhance their properties.…”
Section: Introductionmentioning
confidence: 99%